Computational techniques in chemical process simulators - Hussain, Mohd Azlan (Malaysian Journal of Computer Science, 1993)
Chemical process simulation has become an indispensable part of virtually every process design and analysis task. This paper provides a brief outline of these simulators, demonstrating some of the important computational features required in its development and execution. Various mathematical techniques for solving recycle problems are described and their convergence capabilities compared.